Pertanggungjawaban Pidana Anak Sebagai Kurir dalam Tindak Pidana Narkotika - I Wayan Govinda Tantra; Made Minggu Widiantara; Luh Putu Suryani (Jurnal Analogi Hukum, 2020)
The involvement of the child in narcotic crime that becomes a narcotic courier is a series of malicious agreement in conducting illegal narcotics circulation, but in the capacity category of children who become courier, this is one thing That is so concerned that the child has been faced with the law and is classified as a narcotic crime. Based on the explanation above, the problems that will be considered in this study are as follows: 1. how is the legal arrangement for a child to be a courier in a narcotic crime? 2. How is criminal liability for children as a courier in narcotic crime? The type of research used in this study is a type of normative legal research. The analysis technique is that after the collected legal materials are then analyzed using the technique of description, after all required legal materials are fulfilled, analyzed in a qualitative descriptive. Please note that the determination of the child's age in relation to the criminal liability that can be submitted before the proceeding is 12 (twelve) years up to 18 (eighteen) years in accordance with the verdict of the Constitutional Court No. 1/PUUVIII/ 201/021. In the context of child accountability as a drug courier one of them is that narcotics LAW does not restrict the age in the judiciary, both adults and minors, so that children as narcotics courier can still be punished when Children's capabilities that are still limited and are not as perfect as adults.